2016
DOI: 10.1017/s0263034616000380
|View full text |Cite
|
Sign up to set email alerts
|

Electron diffraction on a traveling wave: “Inelastic Kapitza–Dirac effect”

Abstract: In this paper conceptual points regarding electrons elastic (Kapitza-Dirac effect) and inelastic diffraction effect on the different type slowed electromagnetic wave structures/light gratings are considered. From the unified point of view it is analyzed the main works on this subject for last four decades in chronological order, pointing out the essential peculiarity inherent in induced Cherenkov, Compton, and undulator/wiggler processes too. This review article has also a goal to resolve confusion in scientif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Neglecting the last term in eq. ( 2.4) brings us to a known eikonal approximation, which is used, for instance, in the paper [6]. However, in this case we a priori exclude the singularities of the effective potential as a function of longitudinal particle velocity.…”
Section: Jinst 13 C02018mentioning
confidence: 99%
See 1 more Smart Citation
“…Neglecting the last term in eq. ( 2.4) brings us to a known eikonal approximation, which is used, for instance, in the paper [6]. However, in this case we a priori exclude the singularities of the effective potential as a function of longitudinal particle velocity.…”
Section: Jinst 13 C02018mentioning
confidence: 99%
“…For instance, classical motion of a charged particle in standing laser wave has been deeply analyzed in the work [2], while in our paper [3] the effective potential describing the classical particle trajectory in a laser lattice of arbitrary geometry has been derived. Many papers were devoted to the quantum description of particle interaction in nonuniform electromagnetic fields for both nonrelativistic and relativistic cases (see in [4][5][6] and refs. therein).…”
Section: Introductionmentioning
confidence: 99%
“…one can neglect the term ∼ Γ s C s (t) in Eqs. (95) and the dynamics of electron in the wavefields will be described by the following equation [175]:…”
Section: Phase-latticementioning
confidence: 99%
“…Formula (101) for Cherenkov diffraction in a dielectric medium, which had been received forty years ago [108] and included in the monographs [26] and [33], recently has been considered in the paper [175] because of reproduction of electron diffraction effect on a travelling EM wave in a dielectric medium by the authors of the paper [171], nevertheless represented it as a new phenomenon predicted in the paper [171]. Repeating the results of the paper [108] with the main formula (101) in other way of derivation -within the Helmholtz-Kirchhoff diffraction theory (as was mentioned in Introduction, by the method developed in the paper [172]), authors report in the Abstract that they showed on the possibility of electrons diffraction effect on a travelling EM wave in a dielectric medium.…”
Section: Phase-latticementioning
confidence: 99%